2012
DOI: 10.1111/j.1439-0388.2012.01018.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoroughbred racehorse mitochondrial DNA demonstrates closer than expected links between maternal genetic history and pedigree records

Abstract: The potential future earnings and therefore value of Thoroughbred foals untested in the racing arena are calculated based on the performance of their forebears. Thus, lineage is of key importance. However, previous research indicates that maternally inherited mitochondrial DNA (mtDNA) does not correspond to maternal lineage according to recorded pedigree, casting doubt on the voracity of historic pedigrees. We analysed mtDNA of 296 Thoroughbred horses from 33 maternal lineages and identified an interesting tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 20 publications
(40 reference statements)
1
18
0
Order By: Relevance
“…This problem undoubtedly also concerns other breeds, and generally leads to lower mtDNA diversity in dogs in comparison to that of horses, in which dam lines play an important role in breeding. This concerns such breeds as the Thoroughbred, Lipizzan and Arabian, in populations of which 25, 37 and 74 mtDNA haplotypes, respectively, were found (Bower et al, 2013;Kavar et al, 2002;Khanshour and Cothran, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This problem undoubtedly also concerns other breeds, and generally leads to lower mtDNA diversity in dogs in comparison to that of horses, in which dam lines play an important role in breeding. This concerns such breeds as the Thoroughbred, Lipizzan and Arabian, in populations of which 25, 37 and 74 mtDNA haplotypes, respectively, were found (Bower et al, 2013;Kavar et al, 2002;Khanshour and Cothran, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…2). In this context, the results of mtDNA studies in horses, in which pedigree errors are usually identified (Hill et al, 2002;Kavar et al, 2002;Głażewska et al, 2007;Bower et al, 2013), are deserve attention. Of particular interest are the results presented by Hill et al (2000) and Bower et al (2013) on Thoroughbreds; these indicate that increased numbers of pedigree errors and haplotypes are identified when more detailed pedigree data are used.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An analysis of present‐day racehorses shows that this is not always the case. In a study of 281 Thoroughbred racehorses, maternal lineages were shown to contain two or more mitochondrial genotypes (Bower et al . submitted).…”
Section: Introductionmentioning
confidence: 99%
“…submitted). The primary reasons for these discrepancies are historic errors in the General stud book , introduced early in the breed history, most of which can be traced to the foundation of maternal sub‐lineages (Bower et al . submitted).…”
Section: Introductionmentioning
confidence: 99%